Making Science Undergraduates into lifelong learners: a new Information Literacy module to Science curriculum - Somaratna, Sajeewanie D. (My University, 2011)
Information literacy is important to higher education, as it is a part of, and contributor to, lifelong learning. Due to variations in prior education levels, majority of undergraduates who enter the University do not possess skills of using information for their academic purposes and this was evident in library awareness programmes. To enhance the quality of the academic work the importance of embedding an information literacy course to undergraduate curriculum of the faculty of Science was identified by the faculty. As the initial step, an information literacy module was developed by the library. The quality and the relevancy of the module were evaluated by the Dean and a committee of the faculty and it was subjected to the faculty board approval. The faculty board accepted it as one credit, thirty hour practical course which spanned across second semester of the academic year to the first year undergraduates. Two senior professors from the faculty were appointed as faculty advisors and senior academics from the library were selected as resource persons to conduct this course. The course was conducted from March 2010 to July 2010. Undergraduates gained knowledge on various topics related to information skills during the course. Writing successful assignments, academic reading skills, information seeking and searching techniques, evaluation of information sources, academic writing techniques, literature review writing, citation styles and presentation skills were taught supporting the quality learning for higher education purposes. Students were given hands-on experience with all necessary facilities throughout the course. They were assessed by continuous assignments and a final submission of a literature review and a presentation. Initially this enhancement course was limited to fifty students due to resource limitations and 44 students successfully completed the course. According to the student evaluation of the course, all the students believed that the “Information skills development programme- EC1004” will help them to increase the quality of their academic activities. Also they were expecting to apply what they learned from this course for their other subject areas. Students rated this course as one of the best enhancement courses offered by the faculty and the faculty strongly recommended to make this course compulsory to all students in the Faculty of Science.